(untitled) (Bangladesh Pharmaceutical Journal, 2020)
Cardiovascular disease (CVD) is one of the most prominent health issues responsible for global death currently. Just like the diverse causes of its pathophysiology, a plethora of medicines from different classes are used for the treatment and management of CVDs. However, in low and middle income countries like Bangladesh, it’s extremely difficult for patients to adhere to their treatment regimen consisting of multiple drugs from different classes as it is both expensive and inconvenient. In such scenario, a polypill or a combination of drugs containing different type of cardiovascular drugs could significantly improve the management of cardiovascular diseases in Bangladesh. Our aim was to get a real-life perspective of the prospect of commercially available polypill in Bangladesh keeping all its stakeholders such as patients, physicians and retailers in mind. A survey was conducted in two different cities (Dhaka and Comilla) and the data were correlated. We got positive response from patients, physicians and retailers. Also, the physicians came up with various combinations of drugs such as – ACEI (ngiotensin-converting enzyme inhibitors) and ARB (angiotensin II receptor blockers) (35%); ARB and CCB (calcium channel blockers) (25%) and ACEI and CCB (15%). However, disease patterns, available drugs and comorbidities in the two regions showed significant deviations as metro city based patients suffered from more severe form of CVDs. Therefore, further survey in different regions should be conducted to understand the overall disease pattern and to come up with optimum combinations for CVD patients. Beyond this discussion, it was evident that commercially available polypill has a great prospect in Bangladesh against CVDs. Bangladesh Pharmaceutical Journal 23(1): 17-25, 2020